Penggunaan Media Roda Suku Kata Berbantuan Model Pembelajaran Project Based Learning (PjBL) dalam Meningkatkan Hasil Belajar Bahasa Indonesia Siswa Kelas 1 - Apriani, Maria; Helvina, Maria; Bera, Lukas (Universitas Muhammadiyah Magelang, 2026)
This study aims to improve Indonesian language learning outcomes in early reading and writing through the use of syllable wheel media assisted by the Project-Based Learning (PjBL) model for 27 students of grade 1A of SD Inpres Maumere. This study is a Classroom Action Research (CAR) with the Kemmis & McTaggart model design implemented in two cycles, each consisting of planning, implementation, action, observation, and reflection. The results showed an increase in learning completeness from the pre-cycle to the second cycle. The average student score increased from 65.89 in the pre-cycle with a classical completeness of 37%, to 68.96 in the first cycle with a completeness of 63%, and increased again in the second cycle to 80.51 with a completeness of 80.51%. Thus, it meets the success indicators. In addition to learning outcomes, aspects of student attitudes and skills also improved through the syllable poster project activity. In the pre-cycle, only 13 students were active, increasing to 20 students in the first cycle, and reaching 25 students in the second cycle. Overall, the implementation of the syllable wheel media supported by the Project-Based Learning (PjBL) model has proven effective in improving the learning outcomes, skills, and activeness of grade 1A students at SD Inpres Maumere. Project-based, student-centered learning involving visual media provides a more meaningful learning experience for younger students.